1998
DOI: 10.1073/pnas.95.17.9837
|View full text |Cite
|
Sign up to set email alerts
|

Primary activation of interferon A and interferon B gene transcription by interferon regulatory factor 3

Abstract: The family of interferon (IFN) regulatory factors (IRFs) encodes DNA-binding transcription factors, some of which function as modulators of virus-induced signaling. The IRF-3 gene is constitutively expressed in many tissues and cell types, and neither virus infection nor IFN treatment enhances its transcription. In infected cells, however, IRF-3 protein is phosphorylated at the carboxyl terminus, which facilitates its binding to the CBP͞p300 coactivator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
180
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(190 citation statements)
references
References 48 publications
8
180
0
Order By: Relevance
“…Recent studies from several groups have shown that IRF-3 is phosphorylated at the carboxyl-terminal serine cluster in infected cells and translocated to nucleus, whereby it interacts with the transcriptional coactivator, CBP/p300 (22)(23)(24). Overexpression of E1A that targets CBP/p300 inhibited IRF-3-mediated transactivation of IFNA promoter, thus providing additional evidence for the biological role of IRF-3-CBP/p300 interaction (25).…”
mentioning
confidence: 86%
“…Recent studies from several groups have shown that IRF-3 is phosphorylated at the carboxyl-terminal serine cluster in infected cells and translocated to nucleus, whereby it interacts with the transcriptional coactivator, CBP/p300 (22)(23)(24). Overexpression of E1A that targets CBP/p300 inhibited IRF-3-mediated transactivation of IFNA promoter, thus providing additional evidence for the biological role of IRF-3-CBP/p300 interaction (25).…”
mentioning
confidence: 86%
“…Inhibition of PI3K activity enhances poly(I:C)-and LPS-mediated NF-jB but not IRF3 activation in DC IFN-b gene expression requires cooperation between NF-jB [28,29] and IRF3 [30][31][32] transcription factors. Therefore, we quantified the levels of NF-jB and IRF3 DNA-binding activities in nuclear extracts from wortmannin-treated DC versus control counterparts following LPS or poly(I:C) stimulation.…”
Section: Pi3k Inhibition Enhances Ifn-b Synthesis In DC Stimulated Bymentioning
confidence: 97%
“…In line with data on IKKa/b phosphorylation and IjB-a protein degradation, wortmannin treatment increased levels of p65 and p50 translocating in the nucleus 1 h following exposure to poly(I:C) or LPS ( One important feature of the IFN-b gene is that its transcription enhancer consists of four important positive regulatory domains (PRD), PRDI-IV, required for its activation. While NF-jB members bind to PRDII element on human IFN-b promoter, IRF3 binds to adjacent PRDIII and PRDI elements (referred collectively as PRDIII-I) [30,33]. To analyze the direct influence of wortmannin on NF-jB and IRF-3-mediated transcriptional activities, we assessed reporter gene activities using promoters that contain either NF-jB-or IRF3-binding sites in HEK 293T cells stably expressing TLR3 or TLR4/MD2.…”
Section: Pi3k Inhibition Enhances Ifn-b Synthesis In DC Stimulated Bymentioning
confidence: 99%
“…S3). We chose these cells because E1A antagonizes IRF3-dependent activation of IFN-I gene expression (35), thereby making it possible to control IFN stimulation by exogenous introduction of IFN. The expression of AdV Luc or AdV IKKε alone did not lead to the binding of ISGF3 or GAF to an ISRE or GAS element, respectively.…”
Section: Ifn-mentioning
confidence: 99%